Dimensions of Human Wildlife Conflict in Tamil Nadu - Sekar, T. (Indian Forester, 2013)
Human Wildlife Conflict is emerging as a significant wildlife management issue in Tamil Nadu in the last decade. The conflict results in severe impacts on communities in the form of crop depredation, property damage, loss of livestock, human injury and human killing. On the part of wild animals, the sufferance finds expression through retaliatory response from the affected people or the accidents leading to injury or death of the animals. There are many dimensions to the whole issue of Human Wildlife Conflict, which can chiefly be understood in two broad categories viz., wildlife and habitat dimensions and human dimensions. The wildlife and habitat dimensions are natural geographical features of animal habitat, increase in wildlife number, migratory pattern of animals, occurrence of stray/isolated animal population, shrinkage/degradation of habitat and corridors, diminution of habitat quality. Human dimensions include cultivation up to boundary of forests, cropping pattern and intensity, higher road density, railway lines and canals in wildlife habitats, development of human habitat space and urban infrastructure, large human presence in animal-dominated landscapes, life style pattern, retaliatory response from people, unscientific restraint measures, lack of awareness and inadequacy of frontline staff. Various management responses from the Forest Department, which include prevention and mitigation measures have been described.